Improvement of the operation and safety of nuclear power plants - Ghitheeth, Ali Hussein; Mohammed Hayder, Ali; Khalid, Amir; Ngadiron, Zuraidah (Penerbit UTHM, 2020)
This study investigated the importance of heating processes within a nuclear power plant. The application of Fourier’s law of heat conduction enables determining temperature distributions within the nuclear fuel rods. In contrast, convective cooling occurs on the road surface. The coolant, cladding, and fuel temperature distributions through a reactor are determined. In addition to heat transfer in the reactor core, some power plants engage heat exchangers to produce steam that is fed to a turbine-generator to produce electricity. Thermal power plants reject condenser heat to the environment through mechanisms such as cooling towers as according to a consequence of the second law of thermodynamics. These investigations provide a possible modeling approach and load the following control strategies for problematic nuclear power plants to provide an assessment of the concept designs. A load frequency control strategy and average temperature control mechanism are studied to get load following nuclear power plants. This study reports on the development and analysis of some novel versions and approximations of the fractional-order (FO) point reactor kinetics model for a nuclear reactor with slab geometry. These models evolve from the FO point reactor kinetics model, which has been derived from the FO Neutron Telegraph Equation for the neutron transport considering the subdiffusive neutron transport. This study also proposes a water level control system for a nuclear steam generator (SG). The control system consists of a feedback controller and a feedforward controller. The feedback controller comprised in the ﬁrst order, the feedforward controller is of second order, and parameters of the two controllers are linked with the parameters of plant model; thus scheduling is easily implemented in practice. A model was developed for the thermal analysis of closed feedwater heaters in which wet steam is extracted from the steam turbine (and piped into the heater). Application of this model is of relevance to nuclear power plant diagnostics where the ﬂuid ﬂowing through the steam turbine is wet steam,